Measuring the Attitudes Towards the Extended Order in Latvia, Poland and Russia: The Extended Order Index - Joachim Zweynert; Robert Wyszyński; Andreas Polkowski (Hamburg Institute of International Economics (HWWA), 2006)
The increasing gap between the transition countries with regard to both their economic and political performance cannot be explained by their different starting conditions after the breakdown of the Soviet Union alone. Rather, it is due to cultural and historical circumstances that shape the particular tradition and societal environment. The paper aims at providing empirical evidence of the significance of cultural factors in transition processes by testing the degree to which norms of generalised morality prevail in three different post-socialist societies. On the basis of data collected in larger surveys in Latvia, Poland and Russia, it is being tested whether the divide between the Orthodox countries on the one and the Catholic and Protestant countries on the other hand finds an expression in different attitudes towards market and democracy.
Keywords: C42; Z13; Z12; 330; Cultural Economics; Transition; Extended Order